The efficacy and safety of Topiramate in the Treatment of Refractory Epilepsy in children in Paediatric Neurology clinic at Izzat Ali Shah Hospital - Shahzad Haider, Kiran Pervaiz, Komal Noor, Madiha Fayyaz, Sajid Nazir, Lubna Ehtizaz (Journal of Rawalpindi Medical College, 2021)
Objectives: This study has been performed to observe the efficacy & safety of Topiramate in refractory epilepsies in children in Pakistan. Materials and Methods: A cross-sectional prospective consecutive series of children age between (1-14 years) with refractory epilepsy were recruited from the Paediatric Neurology clinic of Izzat Ali Shah Hospital. Epilepsy was classified into Generalized, Focal, and Unknown based on ILAE Classification. Topiramate was added in patients who were refractory to at least two anti-epileptic drugs. The outcome was recorded in four categories i.e total remission, >50% seizure reduction, <50% seizure reduction, and no improvement. Results: Fifty-eight patients were enrolled in the study, but 5 patients were dropped out due to significant side effects. Most of the children were in the age group ranging from 5 to 10 years with predominant boys (n=32). The major type of epilepsy was 53% (n=28) was Unknown, while 36% (n=19) children had Generalized epilepsy and 11% (n=6) had Focal epilepsy. 25% children had total remission, 38% had >50% seizure reduction, 28% had < 50% seizure reduction and 9% had no improvement. Total remission was mostly seen in Focal epilepsy (50%) and least shown in Unknown type (14%) and the difference was significant (Chi-Square test p=0.039). Adverse effects to Topiramate were found in 33 (62%) of the total enrolled patients. Common adverse effects were weight loss in 14(26%), poor appetite in 13(24.5%), and behavioral issues in 6(22.5%) children. Conclusion: Topiramate is an effective anti-epileptic drug (AED) in refractory epilepsy especially with Focal and Generalized onset but is not as effective in other types of Refractory epilepsy. Weight loss and poor appetite were the commonest adverse effects that were reversible after dose reduction.